RBPI and the study of IR : fostering a multifaceted platform for global dialogue, debate and academic cooperation - Ramanzini Junior, Haroldo (2023)
This paper provides an in-depth analysis of the evolving landscape of international politics, the challenges this scenario presents for the field of International Relations (IR) and the pivotal role played by Revista Brasileira de Política Internacional (RBPI) in shaping both academic knowledge and policy frameworks. The study aims to achieve two primary objectives. First, to contextualize the significant shifts in international politics in the last few years, such as the rise of China and the impact of the COVID-19 pandemic, while advocating for interdisciplinary approaches and highlighting the contributions of Latin American, particularly Brazilian, scholars to global academic debates. Second, to trace the history, evolution, and international impact of RBPI since its inception in 1958, emphasizing its role in leveraging the standards of academic publishing in Brazil and Latin America, fostering international collaborations, and influencing policy decisions. The paper proposes that RBPI serves as an indispensable platform for advancing rigorous academic inquiry and offers a more inclusive perspective on international relations, thereby having a lasting impact on both the academic and policy landscapes globally.